Pengaruh Konsumsi Kopi Terhadap Peningkatan Tekanan Darah - Muslimin, Ikhwanul (Jurnal Ilmu Kesehatan dan Gizi, 2025)
Background: Hypertension is one of the most common cardiovascular diseases in society. One of the risk factors for hypertension is coffee consumption which is characterized by the emergence of many outlets or coffee shops and is influenced by massive cultural shifts. Objectives: Writing this literature review aims to determine the effect of coffee consumption on increasing blood pressure based on the results of previous studies. Methods: In the preparation of this article using the literature review method from searching articles through electronic databases published in the last 10 years. Results: From the results of the literature review conducted, it shows that there are two conditions where coffee consumption can have an effect on increasing blood pressure and coffee consumption has no effect on increasing blood pressure. Conclusion: Coffee consumption can have an effect on increasing blood pressure due to the presence of caffeine which has antagonistic properties against endogenous adenosine and can stimulate sympathetic nerves. However, coffee also contains micronutrient compounds to provide protective effects against hypertension, such as polyphenols, magnesium, potassium, niacin, and vitamin E. Further research using experimental methods so that clear evidence is obtained from previous studies.